Helping the Public Understand the Microplastics Issue: Integrating Citizen Science Techniques and Hands-On Education Experiences with Ongoing Microplastics Research. Issue 3 (18th December 2020) - Sanders, Dorothea; Brandes, Jay
Marine microplastic (plastic particles smaller than 5 mm in length) pollution is a recognized and growing threat to the environment. Microplastic particle estimates number in the trillions and are under sampled in ecosystems worldwide (Eriksen et al. 2014, Zhao et al. 2019 ). Sources of microplastics include manufactured particles (fibers, beads, industrial abrasives) or microplastics generated from breakdown of larger plastics through mechanical, photochemical, or biologically mediated degradation (Schwarz et al. 2019 ). Little is known about the fate or effect of microplastics on marine environments thus emphasizing the importance of scientific research. The University of Georgia Skidaway Institute of Oceanography (UGA SkIO) and Marine Extension and Georgia Sea Grant (UGA MAREX) are mapping the distribution and abundance of microplastics in Georgia's coastal waters. There are many challenges to studying microplastic abundances, including intensive sampling and measurement efforts on a temporal and spatial scale that require trained personnel. Volunteer-based research is well suited for studying microplastic pollution. We have developed a successful volunteer-based monitoring program to assist with research efforts. We have established partnerships with environmental programs and groups including the UGA MAREX volunteer program, and the Satilla, Altamaha and Ogeechee Riverkeepers to assist with monitoring efforts. Everyone involved understands the critical importance of proper research technique, strict protocols and training in order to obtain "believable" data. Our research to date suggests that a dedicated, trained group of scientists and volunteers can provide the mechanism for conducting detailed studies of microplastics on a local to regional scale.